Pengaruh Alokasi Dana Desa (ADD) dan Dana Insentif Daerah Terhadap Tingkat Kemiskinan di Kabupaten Konawe Selatan - Rizal Rizal (Indo Publishing, 2026)
Finding out how the Village Fund Allocation and the Regional Incentive Fund affected the poverty rate in South Konawe Regency over the last five years (2020–2025) was the aim of this study. The exploratory multiple linear regression analysis method is used in this study. The study's findings show that (1) the distribution of village funds had no effect and was not significant in relation to the poverty rate in South Konawe district (sig value: 0.151>0.05); (2) the impact of regional incentive funds on the poverty rate in South Konawe district was negative and not significant (sig value: 0.682>0.05); (3) According to the findings of statistical testing, the poverty rate in South Konawe district is unaffected by the simultaneous distribution of village money and regional incentive funds; the R value is 0.772.